Project Report on System Design of Man Machine Interface - MANJUNATH R and RAJIV OHRI (1991)
INTERNAL GUIDE: RANJAN KUMAR, MVJCE EXTERNAL GUIDE: V V KAMESH, PES DRIVES, BHEL
Keywords: Man Machine Interface